Pengaruh Metode Pembelajaran Examples Non Examples Terhadap Hasil Belajar Siswa Pada Pokok Bahasan Dimensi Tiga Ditinjau Dari Kemampuan Penalaran Siswa Kelas XI SMK Muhammadiyah 4 Surakarta Tahun 2016/2017 - Yuniati, Emi; , Dra. Sri Sutarni, M.Pd (2017)
The research aims to examined (1) the effect of learning methods Examples Non-Examples to the learning outcomes of mathematics,(2) the effect of reasoning ability of students to the learning outcomes of mathematics, (3) the interaction between the learning method Examples Non-Examples with reasoning abilities of students on learning outcomes in mathematics. The type of quantitative research is a quasi-experimental design. Population and sample are11th grade student of SMK Muhammadiyah 4 Surakarta. The sampling technique used cluster random sampling. The data collection technique used the test methods and documentation. The data were analyzed using two-way analysis of variance with different cells. The results of the research with α = 5% is (1) there are significant influence of learning methods Examples Non-Examples of the learning outcomes of mathematics, (2) there are significant influence reasoning ability of mathematics to the learning outcomes of mathematics, (3) there are no interaction between the learning method Examples Non Examples and mathematical reasoning abilities of the mathematics learning outcomes.